Diseño de sistema de recuperación de calor de aire caliente de desecho para calentamiento y vaporización de agua en la compañía Vidrio Andino S.A. (2019)
For developing the present grade project, was necessary to have knowledge and develop a detailed analysis of Vidrio Andino S.A. company necessities focused on the improvements opportunities for heating recovery. The project initiated with the resource stage and process analysis on which was found heating losses in the thermal conditioning inside the furnace potentially usable, as well as a thermal energy consumption highlighted used for the vaporization of water used on the conditioning of batch raw materials. Once the potential heating recovery was found and the final receipt of this energy, it has been proceed to make a detailed characterization of the sources and required parameters needed by the process in order to have all the complete information to make a properly designed of the heating recovery system. The detailed design of the heating recovery system was one of the important and challenging stages due that in this stage were developed all the estructural, materials, and process calculations that will guarantee an properly working and solving of the required necessities.